The Potential of E-Learning in Understanding Concepts in Science and Physics Education: A Bibliometric Analysis - Adrian Bagas Damarsha; Nadi Suprapto; Elvia Reza Lutfiani; Siti Nur Aisah; Husni Mubarok; Alif Syaiful Adam (Universitas Negeri Surabaya, 2026)
Objective: The objective of this study is to describe trends, contributions, developments, and research opportunities in e-learning for conceptual understanding in physics and science education. Method: The research method employed was bibliometric analysis using the Scopus database. Data were obtained from the Scopus database using the search terms “E-Learning” AND “Physics Education” OR “Science Education” AND “Conceptual Understanding,” yielding 2,735 documents. The Scopus database was filtered by year, document type, and language, resulting in 2,363 documents for analysis. Results: The results indicate that research on e-learning’s impact on conceptual understanding in physics or science education has been a trend over the past ten years. The top contributing authors are H, Gwo-Jen; S, Niwat; K, Heru; and S, Andi, while the top affiliations are Indonesia University of Education, Padang State University, and Malang State University. Current developments in e-learning have been categorized as artificial intelligence, so the opportunity for data-driven research lies in developing artificial intelligence for learning. Novelty: Technological transformation has impacted the world of education, particularly in strategies to improve students’ conceptual understanding. This study presents a bibliometric mapping of e-learning research related to conceptual understanding in physics and science education. This study differs from previous research, which has not presented a thematic evolution to guide future research.